Perceived Stress, Knowledge, and Preventive Behaviors in Indian versus US-based Participants During COVID-19: A Survey Study - Sinharoy, Ankita; Pal, Shekhar; Das, Jishu; Mondal, Pritish (Frontiers in Public Health, 2021)
Rationale: India and the US, the worst affected countries by COVID-19, experienced very different pandemic courses. By 2020, COVID-19 cases had steadily declined in India, while the fight continued in the US. The people of India and the US perhaps perceived threats very differently, influenced by their knowledge, available healthcare resources, and social security. We conducted an online survey study to compare COVID-related perceptions between Indian (IND-P) versus US-based participants (US-P). Methods: COVID-related perceptions such as stress, knowledge, and preventive behaviors were measured with specific questionnaires, and normalized scores were computed. T-tests were used to compare the perception scores, while the Kruskal-Wallis-H (KWH) tests were used to compare socio-economic distributions between the two countries. Generalized linear model (GLM) adjusted for sociodemographic confounders estimated the association between country of residence and COVID-perception. Results: IND-P (N=242) were younger and male-dominated compared to US-P (N=531) (age: KWH=97.37,p<.0001, gender: KWH=140.38,p<.0001). Positive attitudes towards preventive guidelines were associated with higher perceived risk and stress (r=0.35, p<.001, and r=0.21, p<.001, respectively), but not with the knowledge (r=-0.05, p=.14). Compared to US-P, IND-P had lower knowledge (5.19±1.95 vs. 7.82±1.35; t-test:p<.0001), higher stress (7.01± 1.51 vs. 6.07±1.61; t-test:p<.0001), and better adherence to preventive guidelines (8.84±1.30 vs. 8.34±2.09; t-test:p=.0006). GLM demonstrated a significant association between country and all three COVID-perception metrics. Conclusion: IND-P experienced higher stress levels and perceived threat during COVID-19 than US-P, perhaps due to a lack of faith in the healthcare system and insecurity. Despite lower knowledge, IND-P had better acceptance of preventive guidelines than US-P.